On the reconstruction of some Indo-European text fragments in Baltic and Slavic languages - Eckert, Rainer (Baltistica, 2022)
Different kinds of reconstruction are objects of investigation in this paper which mainly focuses on fixed combinations of words, phraseological units, set phrases and components of texts. Fragments of Baltic and Slavic texts are examined.